How to Create Effective Problem Situations in Primary School Mathematics Teaching - Yang, Tingting (Journal of Education and Educational Technologies, 2023)
Mathematics is a subject with strong logical thinking. It is difficult for primary school students to learn. If there is no reasonable and effective teaching method, it may lead to students' resistance and loss of interest in mathematics learning. In order to improve this problem and meet the requirements of the new curriculum reform, the teaching methods of primary school mathematics have been reformed. By creating effective problem situations, students' learning interests have been aroused, and their subjective initiative has been given full play. In this situation, teachers and students interact closely, effectively cultivate students' innovative thinking ability, more profound understanding and memory of knowledge, and effectively improve the quality of mathematics teaching. This paper explores the creation of effective problem situations in primary school mathematics teaching at a deep level, and actively implements them in combination with teaching requirements.